2014
DOI: 10.1089/sur.2011.039
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Species-Specific Hospital Mortality Rate for Intra-Abdominal Infections

Abstract: In addition to age and intrinsic patient factors, the presence of specific bacterial organisms independently predicts death in patients with non-appendiceal IAI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…The distribution of isolated pathogens, in our study, was identical to other reports, being Escherichia coli the most frequent, independently of the classification used [5, 15, 21, 3941]. The prevalence of monomicrobial IAIs (62%) was much superior in comparison to the studies by Claridge et al [41] (41%) and Shah et al [42] (33%).…”
Section: Discussionsupporting
confidence: 86%
“…The distribution of isolated pathogens, in our study, was identical to other reports, being Escherichia coli the most frequent, independently of the classification used [5, 15, 21, 3941]. The prevalence of monomicrobial IAIs (62%) was much superior in comparison to the studies by Claridge et al [41] (41%) and Shah et al [42] (33%).…”
Section: Discussionsupporting
confidence: 86%
“…continues to be debated 262728. Some studies have suggested that the isolation of Enterococcus in patients with IAIs results in treatment failure or increased mortality,293031 while others demonstrated no association with mortality 3233. Furthermore, some studies have shown equivalent therapeutic effects among empiric antibiotic regimens, regardless of the antimicrobial activity against enterococci 34353637.…”
Section: Discussionmentioning
confidence: 99%
“…Escherichia coli the most frequent independently of the classification used. 9,20,28,44,64,66 The prevalence of monomicrobial IAIs (62%) was much superior by comparison to the studies by Claridge et al 66 (41%) and Shah et al 67 (33%).…”
Section: Discussionmentioning
confidence: 70%